1997
DOI: 10.1095/biolreprod57.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Source of Inhibin in Ovine Fetal Plasma and Amniotic Fluid during Late Gestation: Half-Life of Fetal Inhibin1

Abstract: Immunoactive inhibin (ir-inhibin) concentrations were determined in chronically catheterized sheep between 120 and 145 days gestation. Maternal plasma ir-inhibin concentrations remained basal (0.19 +/- 0.05 ng/ml) throughout the period of study. Immunoactive inhibin concentrations in male and female fetal plasma were elevated above those observed in maternal plasma, with the concentrations in plasma of male fetuses (7.38 +/- 0.04 ng/ml) being significantly greater (p < 0.001) than those in female fetuses (1.07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Circulating concentrations of ir-inhibin in both male and female ovine fetuses have been reported to be higher than those in maternal circulation [17,19]. It was reported that gonadectomy in the fetus caused a rapid decline in circulating ir-inhibin levels, suggesting that the gonads were the primary source of circulating ir-inhibin [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating concentrations of ir-inhibin in both male and female ovine fetuses have been reported to be higher than those in maternal circulation [17,19]. It was reported that gonadectomy in the fetus caused a rapid decline in circulating ir-inhibin levels, suggesting that the gonads were the primary source of circulating ir-inhibin [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that gonadectomy in the fetus caused a rapid decline in circulating ir-inhibin levels, suggesting that the gonads were the primary source of circulating ir-inhibin [19]. The equine fetal gonads of both sexes have attracted much interest because of the remarkable enlargement in size as a result of massive number of interstitial cells between the third and ninth months of gestation [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adrenal gland has been postulated to be a main source of circulating inhibin in the chicken embryo (Rombauts et al, 1994). With respect to mammals, the fetal gonad is likely to be a major source of inhibin in male but not in female ovine fetal plasma (Miller et al, 1997). In the male ovine fetus, gonadectomy considerably decrease fetal circulating inhibin.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of progesterone were measured by the ELISA method described by Groves et al (1990). Concentrations of inhibin were determined using the method of Beard et al (1990), modified by using the antiserum prepared by Robertson et al (1989) and validated for use in sheep by Miller et al (1997). Details of reagents and assay validation criteria for each of these assays are given (Table 1).…”
Section: Hormone Assaysmentioning
confidence: 99%